2021
DOI: 10.1039/d0tc05281g
|View full text |Cite
|
Sign up to set email alerts
|

An organic–inorganic hybrid semiconductor for flexible thin film transistors using molecular layer deposition

Abstract: Indium oxide and indicone hybrid films consisting of indium oxide and organic aromatic linker are grown by molecular layer deposition (MLD) using bis(trimethylsilyl)amido-diethyl Indium (INCA-1) as the indium precursor, hydrogen...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 54 publications
1
10
0
1
Order By: Relevance
“…Flexible substrates, such as polyimide (PI), polyethylene terephthalate (PET), polyethylene naphthalate (PEN), polytetrafluoroethylene (PTFE), and polydimethylsiloxane (PDMS) are used instead of the conventional rigid substrates to realize flexible electronics. However, since flexible substrates generally have lower thermal resistance than that of rigid substrates (i.e., silicon and glass), it is relatively difficult to implement stable transistor operation [46][47][48][49]. Metal-oxide semiconductors that can be processed at low temperatures (<350 • C) and offer stable electrical performance are promising active materials for flexible transistors.…”
Section: Flexible Devicementioning
confidence: 99%
“…Flexible substrates, such as polyimide (PI), polyethylene terephthalate (PET), polyethylene naphthalate (PEN), polytetrafluoroethylene (PTFE), and polydimethylsiloxane (PDMS) are used instead of the conventional rigid substrates to realize flexible electronics. However, since flexible substrates generally have lower thermal resistance than that of rigid substrates (i.e., silicon and glass), it is relatively difficult to implement stable transistor operation [46][47][48][49]. Metal-oxide semiconductors that can be processed at low temperatures (<350 • C) and offer stable electrical performance are promising active materials for flexible transistors.…”
Section: Flexible Devicementioning
confidence: 99%
“…In the few additional studies involving the 4d or 5d transition metals, Nb‐based films have been deposited from Nb(OEt) 5 in combination with HQ, [ 421 ] Mo‐based films from molybdenum hexacarbonyl together with 1,2‐ethanedithiol (EDT), [ 242,243 ] 1,4‐butanedithiol, and BDT, [ 243 ] and In‐based films from bis(trimethylsilyl)amidodiethylindium (INCA‐1) and HQ. [ 369,422,423 ] The as‐deposited In–HQ films showed a structural change upon exposure to ambient air and were found promising as flexible transparent films. [ 424 ] Tin‐based hybrid films have been deposited from Sn–TDMA together with GL, [ 220,425 ] and EG, [ 220 ] and also from HS–Sn with HQ.…”
Section: Brief Account Of Ald/mld Processes Developedmentioning
confidence: 99%
“…One is to exploit the full potential of TFTs with ALD‐derived n ‐channel oxide channels to verify the feasibility of using them as non‐planar structures such as vertical TFT (VTFT) 72–75 in AR/VR displays or three‐dimensional NAND flash memory. The other combines LTPS‐compatible high‐performance TFTs with an ALD‐derived n ‐type semiconducting channel layer through novel structures including heterostructures, 22–25 bilayers, 26 and hybrid channels 27,28 …”
Section: Ald‐derived N‐channel Oxide Tftsmentioning
confidence: 99%
“…In this review, recent research on ALD‐derived semiconducting oxides and insulating dielectric films and their suitability for high‐performance oxide TFTs is described. The basic principles of ALD and earlier approaches to flexible oxide TFTs were reviewed in 2018 by Sheng et al 20,21 We therefore focused on studies of ALD‐based oxide TFTs reported since 2018, highlighting the use of novel structures including heterostructures, 22–25 bilayers, 26 and hybrid channels 27,28 in the development of LTPS‐compatible high‐performance oxide TFTs. Efforts to create 3D applications of ALD‐derived oxide TFTs, including vertical TFTs and complementary metal–oxide semiconductor (CMOS) TFTs for AR/VR, monolithic 3D devices, and 3D memory are also covered.…”
Section: Introductionmentioning
confidence: 99%